2011
DOI: 10.3109/0886022x.2011.568148
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carnitine in Preventing Renal Damage Developed as a Result of Infrarenal Aortic Ischemia–Reperfusion

Abstract: Background: This study was designed to use carnitine for preventing deposition of end products of lipid peroxidation in rat models in the prevention of ischemia-reperfusion (IR) damage frequently seen following operations of infrarenal abdominal aorta (AA). Methods: Forty male rats of Sprague-Dawley type were evenly (n = 8) randomized to five groups: sham laparotomy (SHAM), carnitine control (CC), aortic IR (AIR), AIR + low-dose carnitine (AIR+LDC), and AIR + high-dose carnitine (AIR+HDC). Results: Compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Some researchers also found that carnitine is effective in renal ischemia injury2,3, prevent early graft dysfunction4 and is partially preventing renal damage developed as a result of ischemia reperfusion5. Carnitine is also combinated with 5-aminoimidazole-4-carboxyamide ribonucleoside that enhancing energy metabolism and provides a novel modality to treat renal ischemia/reperfusion injury16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers also found that carnitine is effective in renal ischemia injury2,3, prevent early graft dysfunction4 and is partially preventing renal damage developed as a result of ischemia reperfusion5. Carnitine is also combinated with 5-aminoimidazole-4-carboxyamide ribonucleoside that enhancing energy metabolism and provides a novel modality to treat renal ischemia/reperfusion injury16.…”
Section: Discussionmentioning
confidence: 99%
“…In the prevention of injury after ischemia many antioxidants and free radical scavengers such as carnitine, a water-soluble quaternary ammonium structure and naturally present in the cells of animal origin, have protective effect on renal ischemia injury2,3. Carnitine also prevents early graft dysfunction4 and is partially preventing renal damage developed as a result of ischemia reperfusion5. This present study was performed to investigate the any actual benefit of the carnitine alone or in conjuction with other cold preservation solutions.…”
Section: Introductionmentioning
confidence: 99%